Edukasi dan Pendampingan Pembuatan Inovasi Eco Enzyme KWT Tunas Mandiri - Nurdiani, Ulfah; Karim, Akhmad Rizqul; Mandamdari, Alpha Nadeira; Utami, Dewanti Risa; Saputro, Wahyu Adhi (Penerbit Widina, Widina Media Utama, 2025)
The purpose of this community service activity is to provide education and assistance in making eco-enzymes, one of the benefits of which is as an organic fertilizer. This is based on one of the active women's farmer groups in Banyumas, namely KWT Tunas Mandiri, regarding the problem experienced, namely the still low utilization of waste around KWT Tunas Mandiri. Participants in this community service activity were 15 members of KWT Tunas Mandiri and the activity was carried out in June 2025. The method applied in this community service activity is service learning which includes five stages of community service activities from preparation to evaluation. The initial stage is conducting a problem survey, then continued to prepare appropriate solutions and continued with education through socialization and counseling until it ends with direct practice activities for making eco-enzymes. Based on the results of community service activities, there has been an increase in knowledge and skills about making eco-enzymes for KWT Tunas Mandiri. The participants of the community service activity have also been able to practice making them independently at their respective homes. This is also proven by an increase in knowledge from the results of the pre-test and post-test which increased by 20%.ABSTRAKTujuan kegiatan pengabdian ini adalah memberikan edukasi dan pendampingan pembuatan eco-enzyme yang memiliki manfaat salah satunya sebagai pupuk organik. Hal ini didasarkan pada salah satu kelompok wanita tani yang aktif di Banyumas adalah KWT Tunas Mandiri mengenai permasalahan yang dialami yaitu masih rendahnya pemanfaatan sampah yang ada di sekitar KWT Tunas Mandiri. Peserta kegiatan pengabdian ini adalah anggota KWT Tunas Mandiri sejumlah 13 orang dan pelaksanaan kegiatan dilakukan pada Bulan Juni Tahun 2025. Metode yang diterapkan dalam kegiatan pengabdian ini adalah service learning yang meliputi lima tahapan kegiatan pengabdian dari persiapan hingga evaluasi. Tahapan awal adalah melakukan survey permasalahan kemudian dilanjutkan menyiapkan solusi yang tepat dan dilanjutkan dengan edukasi dengan cara sosialisasi dan penyuluhan hingga diakhiri dengan kegiatan praktik langsung pembuatan eco enzyme. Berdasarkan hasil kegiatan pengabdian kepada masyarakat terjadi peningkatan pengetahuan dan keterampilan tentang pembuatan eco enzyme bagi KWT Tunas Mandiri. Para peserta kegiatan pengabdian juga sudah bisa melakukan praktik pembuatan secara mandiri di rumah masing-masing. Hal ini juga terbukti bahwa terjadi peningkatan pengetahuan dari hasil pre-test dan post-test yang mengalami kenaikan sebesar 20%.